Citation studies in English vs. Indonesian research article introductions (RAIs) in the history discipline - Warsidi Warsidi; Andi Muhammad Irawan; Zifirdaus Adnan; Iskandar Abdul Samad (Universitas Syiah Kuala, 2023)
Citation studies in research articles (RAs) have been widely conducted worldwide, but such studies rarely compared English and Indonesian RAs, especially within the history discipline. Therefore, the researchers intended to analyze and compare citations in English and Indonesian research article introductions (RAIs) in the history discipline using a genre approach for the analysis and a descriptive qualitative approach for the reports. In this regard, 30 RAIs from both data sets were analyzed using two different frameworks: one is to identify citation ways and, the other one is to analyze citation types. The results revealed that English and Indonesian authors tended to employ descriptions more than other techniques when citing sources. However, English authors employed this technique more than Indonesian authors. In addition, both English and Indonesian authors also used a non-integral type more frequently than the integral counterpart, but English authors employed this type more frequently than Indonesian authors. Thus, these results conclude that although both English and Indonesian authors tended to assimilate their citations and avoid integrating them, English authors still employed this citation technique and type more frequently than Indonesian authors.